Floating exchange rates : theories and evidence - MacDonald, Ronald (London : Boston : Unwin Hyman, 1988)
This volume, composed of four parts covers in a detailed study international financial operations today. Part I summarizes the development war-payments practices difficulties encountered in this field. Part II provides an up-to-date technical description of international financial restrictions. The author defines in detail various payments methods, which will prove enlightening to non specialists and graduate students in this field. Part III is encyclopedic and summarizes the details of exchange practices and restrictions of each country of the trading world. This part composes the bulk of the book, about two hundred pages, and is better adapted for reference use than for continuous reading. Part IV presents the analysis of the problem and engages in a series of important suggestions for the improvement of the international financial chaos.
Includes index.
Includes bibliographical references: p. [298]-316
usc 08/05/2018
Loans
Keywords: Foreign exchange; Foreign exchange rates